Preparing to be Allies: Narratives of Non-Indigenous Researchers Working in Indigenous Contexts - Brophey, Alison; Raptis, Helen (Alberta Journal of Educational Research, 2017)
Insensitive research approaches have resulted in damaged relationships between non-Indigenous researchers and Indigenous communities, prompting scholars and funding agencies to call for more culturally compatible research methods. This paper addresses the qualities, skills and knowledge developed by six non-Indigenous researchers as they built–and continue to maintain–respectful research relationships with Indigenous communities. Also discussed are the important formative experiences that have shaped the six researchers in their ongoing work. Findings presented in this paper are synthesized from a larger research project undertaken using narrative approaches to data collection and analysis. Des approches de recherche insensibles ont nuit aux relations entre les chercheurs non autochtones et les communautés autochtones, ce qui a incité les universitaires et les organismes de financement à exiger des méthodes de recherche plus respectueuses et mieux adaptées aux cultures. Cet article porte sur les qualités, les habiletés et les connaissances qu’ont développées six chercheurs non autochtones en établissant et en maintenant des relations de recherche avec des communautés autochtones. Nous discutons également des expériences formatrices qui ont marqué les six chercheurs et façonné leur travail en cours. Les résultats présentés dans cet article sont synthétisés d’un plus grand projet de recherche reposant sur des approches narratives à la collection et à l’analyse de données.